Pengaruh Nilai pH yang Berbeda Terhadap Hasil Penetasan Telur Ikan Nilem (Ostheochillus vittatus) - Febriyana Novita Damayanti; Agoes Soeprijanto; Dailami, Muhammad (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2023)
The high market demand for nilem fish must be balanced with good hatcheries. One of the success factors of hatcheries is the hatchability of fish eggs. Egg hatchability is the percentage of eggs that hatch after a certain time. The hatchability of fish eggs is certainly influenced by several factors, one of which is pH which affects the chorionase enzyme in eggs. The purpose of this study was to determine the effect of different pH in the media on the hatching of nilem fish eggs. The research method used is an experimental method with a complete randomized design (RAL). The mainmain parameters used in this study are embryo development, hatching rate (HR), larval abnormality, and larval survivale (SR) and the supporting parameters used in this study are temperature and DO. The results showed that pH treatment had a significantly different effect on the hatching of nilem fish eggs. The best result of HR in nilem fish was 95% at pH (9) and the lowest result of HR in nilem fish was 15% pH (11). The hatchability relationship of eggs given different treatments formed a quadratic equation. The results showed that pH treatment affects the SR value. The best SR result of nilemfish larvae was 93% at pH (9) and the lowest SR result was 0% at pH (11). The survivale rate relationship of eggs given different treatments formed a quadratic equation.